Pelatihan Pembuatan Kerajinan Tangan Meronce sebagai Sarana Kreativitas Anak di Panti Asuhan Abadi Aisyiyah Parepare - Mas’ud B; Malik, Marwati Abd.; Malik, Bismar; Saputri, Amina; Ardiana; Utami, Arlinda; Amaliah, Eka; Khaerati SN, Esy Nurul; Fakhiratunnisa; Pahe, Irayanti Wila; Khaerunnisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The beading handicraft training at Abadi Aisyiyah Orphanage in Parepare City was initiated due to the children's monotonous daily routines and limited facilities for developing their creative skills. This activity aimed to provide the children with new experiences, enhance their fine motor skills, creativity, and self-confidence. A total of 30 children from the Abadi Aisyiyah Orphanage in Parepare City participated in this activity. The training was conducted over three days, with the first day focused on demonstrating the making of bracelets and rings, followed by a creative session where the children could make crafts according to their imagination. The second day continued with demonstrations of making phone straps and keychains, followed by similar creative activities. Data collected showed a significant increase in the children's fine motor skills and self-confidence after the training. On the third day, the products were marketed, and the event was concluded. Following the training, there was a 25% increase in creativity, a 40% improvement in fine motor skills, and a 5% boost in self-confidence. Additionally, the sales of the handicraft products made by the children not only enhanced their marketing skills but also yielded a 100% profit. The profits were used to purchase beading tools and materials, ensuring the sustainability of this creative activity in the future. This activity underscores the importance of providing creative facilities for children's development in orphanages and demonstrates the positive impact of engaging in creative activities on skill development and self-confidence.